2015
DOI: 10.1007/s11695-015-1600-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Plication (LGCP) Vs Sleeve Gastrectomy (LSG): A Single Institution Experience

Abstract: LGCP patients required more redo surgery. Weight loss was greater in LSG group at 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
3
18
0
1
Order By: Relevance
“…With the improvement of surgical techniques and endostapling devices, LSG had become a popular procedure for morbid obesity. According to previous studies [12][13][14][15][16][17][18][19][20][21], 53.8-80% of excess weight loss was obtained at 12 months postoperatively, and a similar result of 66.08% was noted in our study. However, the resection of the stomach with a long staple line was also accompanied by the innate risk of postoperative bleeding and leakage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With the improvement of surgical techniques and endostapling devices, LSG had become a popular procedure for morbid obesity. According to previous studies [12][13][14][15][16][17][18][19][20][21], 53.8-80% of excess weight loss was obtained at 12 months postoperatively, and a similar result of 66.08% was noted in our study. However, the resection of the stomach with a long staple line was also accompanied by the innate risk of postoperative bleeding and leakage.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the risk of bleeding or leakage might be reduced. As for weight reduction in LGCP, previous studies [12][13][14][15][16][17][18][19][20][21] showed that a 42.1-58.8% excess weight loss was obtained at 12 months after surgery. In our study, a comparable outcome of 48.02% was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, data comparing LGCP to LSG showed that LGCP is less effective in terms of weight loss already at midterm results. 12,13 In the present series, weight loss was considered unsatisfactory in patients with %EBL < 50%. This was always associated with evidence of gastric prolapse.…”
Section: Discussionmentioning
confidence: 85%
“…In the study of Verdi et al [13], 12 out of the 13 reported major morbidities are of the same Bnature^, thus gastric wall prolapse/invagination. We could not ascertain there was an intrinsic flaw in LGCP that was related to this kind of complication or these major morbidities were just caused by inexperience.…”
Section: Discussionmentioning
confidence: 95%